Medium-sized Sin− (n = 14–20) clusters: a combined study of photoelectron spectroscopy and DFT calculations. (8th August 2018) - Wu, Xue; Liang, Xiaoqing; Du, Qiuying; Zhao, Jijun; Chen, Maodu; Lin, Miao; Wang, Jiashuai; Yin, Guangjia; Ma, Lei; King, R Bruce; von Issendorff, Bernd
Abstract: Size-selected anionic silicon clusters, ( n   =  14–20), have been investigated by photoelectron spectroscopy and density functional theory (DFT) calculations. Low-energy structures of the clusters are globally searched for by using a genetic algorithm based on DFT calculations. The electronic density of states and vertical detachment energies have been simulated by using ten DFT functionals and compared to the experimental results. We systematically evaluated the DFT functionals for the calculation of the energetics of silicon clusters. CCSD(T) single-point energies based on MP2 optimized geometries for selected isomers of are also used as benchmark for the energy sequence. The HSE06 functional with aug-cc-pVDZ basis set is found to show the best performance. Our global minimum search corroborates that most of the lowest-energy structures of ( n   =  14–20) clusters can be derived from assembling tricapped trigonal prisms in various ways. For most sizes previous structures are confirmed, whereas for a new structure has been found.